Urgency of the integration of religion and knowledge for the development of Muslim character - Thoha, Anis Malik (2011)
Almost, if not all, modern educational institutions of the west, and followed consciously or unconsciously by many of that of the east (including some Muslim countries such as Indonesia), strongly “believe” that religion and knowledge or science are two different entities that are mutually exclusive and can never meet each other, let alone be integrated or reconciled together. Religion, according to this “belief”, belongs to the domain of belief (which is irrational), whereas knowledge or science belongs to the domain of reason. As a result of this dichotomy, educational curricular, including that of teaching-learning religions and study of religions, at all educational levels have been designed to be religiously neutral. Indeed, the issue of relationship between religion and science or knowledge has drawn a lot of attentions from scholars and thinkers throughout the history. Theories have been introduced to meet this issue, which include, among the others, Conflict, Independence, Dialogue, and Integration. The question at this juncture is whether this dichotomous reasoning is plausible or epistemologically tenable. As such, this paper tries to discuss and analyze this issue with special reference to Islamic context.